Hydrogen Sulfide and Silicon Together Alleviate Chromium (VI) Toxicity by Modulating Morpho-Physiological and Key Antioxidant Defense Systems in Chickpea (Cicer arietinum L.) Varieties - Singh, Deepti; Singh, Chandan Kumar; Siddiqui, Manzer H.; Alamri, Saud; Sarkar, Susheel Kumar; Rathore, Abhishek; Prasad, Saroj Kumar; Singh, Dharmendra; Sharma, Nathi Lal; Kalaji, Hazem M.; Brysiewicz, Adam (Frontiers in Plant Science, 2022)
Extensive use of chromium (Cr) in anthropogenic activities leads to Cr toxicity in plants causing serious threat to the environment. Cr toxicity impairs plant growth, development and metabolism. In the present study, we explored the effect of NaHS (a hydrogen sulfide; [H2S], donor) and silicon (Si), alone or in combination, on two chickpea (Cicer arietinum) varieties (Pusa 2085 and Pusa Green 112), in pot conditions under Cr stress. Cr stress increased accumulation of Cr reduction of the plasma membrane (PM) H+-ATPase activity and decreased in photosynthetic pigments, essential minerals, relative water contents (RWC), and enzymatic and non-enzymatic antioxidants in both the varieties. Exogenous application of NaHS and Si on plants exposed to Cr stress mitigated the effect of Cr and enhanced the physiological and biochemical parameters by reducing Cr accumulation and oxidative stress in roots and leaves. The interactive effects of NaHS and Si showed a highly significant and positive correlation with PM H+-ATPase activity, photosynthetic pigments, essential minerals, RWC, proline content and enzymatic antioxidant activities (catalase, peroxidase, ascorbate peroxidase, dehydroascorbate reductase, superoxide dismutase, and monodehydroascorbate reductase). A similar trend was observed for non-enzymatic antioxidant activities (ascorbic acid, glutathione, oxidized glutathione, and dehydroascorbic acid level) in leaves while oxidative damage in roots and leaves showed a negative correlation. Exogenous application of NaHS + Si could enhance Cr stress tolerance in chickpea and field studies are warranted for assessing crop yield under Cr-affected area.